SISTEM INFORMASI KLINIK GIGI CN-28 THE CN-28 DENTAL CARE INFORMATION SYSTEMS - , KINANTHI SETYANINGRUM; , Sigit Priyanta, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
CN-28 dental care is a dental care placed at Cokroaminoto Street No. 28, Batang, Central Java. This dental care has a lot of patients that come from around Batang. As it has a lot patients, manual data recording that was used by this dental care might cause writing errors and data storage inefficiency. Based on this kind of problem, an information system was needed to help the dentist managing the data, so that it would be well-placed. As the data well-placed, it could help the dentist to give the health services efficiently. Information system that could help CN-28 dental care was built by using Laravel framework and MySQL database. The information system handled each patientsâ data management processes, patientsâ check-up data, diagnostic data, treatments data, and financial reports in tables that could be printed.